Habilidades sociais e qualidade de vida de professores do ensino fundamental - Esteves, Marcela Mangili (Universidade Federal de São Carlos, 2018)
The working conditions of elementary school teachers are known to be of low quality, compromising their physical and mental health and, consequently, their quality of life. One factor that contributes to quality of life is a good repertoire of social skills, which may contribute to more productive and satisfactory interpersonal relationships, including the quality of teacher-student interactions and, thus, to the teaching-learning process. The present study analyzed indicators of quality of life (QOL) and social skills (SS) of teachers, taking into account sociodemographic variables which could moderate this relation. Participants were 85 teachers of 1st to 5th grade students, working in public schools in two cities in the interior of São Paulo, who completed the Social Skills Inventory (IHS-Del-Prette-2016), the Quality of Life Questionnaire (WHOQOL-abbreviated) and two sociodemographic questionnaires (Brazil Socioeconomic Criteria and "Getting to know a little more about you"). Descriptive analyses were performed for the SS and QOL measures as well as inferential analyses of the correlation between these variables, adopting a level of significance of p≤0.05. The results allow us to conclude that there is a positive correlation between SS and QOL, mainly between the SS General Score, Factor 1 (Conversational skills) and Factor 2 (Expression of positive feelings) with the General Score of QOL, Domain 2 (Psychological) and Domain 4 (Environment). The main changes that accented after controlling the variables age, training, experience as a teacher and socioeconomic class were the increase in the correlations of Factor 1 (Conversational skills) with the General Score QOL, as well as with Domain 4 (Environment). In addition, Factor 1 (Conversational skills) began to correlate with Domain 1 (Physical). On the other hand, Factor 2 (Expression of positive feelings) no longer correlated with any other variable of QOL, after controlling to socioeconomic class and age and, no longer had a significant correlation with Domains 1 (Physical) and 4 (Environment). The variables "number of students per classroom" and "workload" did not moderate the relationship between SS and QOL. It can be concluded that there is a relation between HS and QV of primary school teachers and that some sociodemographic variables may be moderators of this relationship, while others do not. Implications for future research based on results are discussed.
Social skills and quality os life of elementary school teachers
Keywords: Habilidades sociais; Qualidade de vida; Professor de ensino fundamental; Social skills; Quality of life; Elementary school teacher; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::RELACOES INTERPESSOAIS